Interdyscyplinarne konteksty animacji kultury = Interdisciplinary contexts of cultural animation - Idzikowski, Bogdan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Cultural animation as a thought and teaching practice has numerous interdisciplinary contexts - genetic, functional, theoretical, objective-substantial and subjective-social. This multifaceted phenomenon of cultural animation determines it as peculiar and upto-date in the rapidly changing social reality. The recognition of cultural animation multiparadigmatisation lets us define it from various theoretical perspectives and place it in various disciplinary areas.
Keywords: pedagogika; nauki społeczne; animacja kulturalna